Efficacy and Safety of Azithromycin with Various Cephalosporins Used in Treatment of Lower Respiratory Tract Infection - Khan, Imran Ahmad; Rani. R.H, Shobha; Subramanyam, Geetha (Indian Journal of Pharmacy Practice)
Both macrolides as well as cephalosporins are widely used in the treatment of various lower respiratory tract infections either alone or in combination. The most commonly prescribed macrolide is azithromycin, generally in combination with different cephalosporins. The objectives of the present study were to find out the different combinations of azithromycin and cephalosporins generally prescribed, compare their efficacy, safety (adverse drug reactions) and cost. A prospective study was conducted in the medicine ward at St. Martha's Hospital, Bangalore. The data was analyzed to interpret different parameters of the study. Efficacy was determined based upon the clinical response (reduction in symptoms) and length of hospital stay. Safety was determined by assessing the occurrence of ADR and their severity. Cost of treatment was calculated by cost effective analysis. In the study period, 88 patients were included based on the inclusion criteria. Results revealed that different combinations prescribed were azithromycin + cefotaxime, azithromycin + ceftriaxone and azithromycin + cefuroxime. The most commonly prescribed combination was found to be cefotaxime with azithromycin. The cefotaxime group showed statistically significant difference in the reduction of clinical symptoms thereby indicating greater efficacy. 18% of the patients experienced ADRs which were mild in nature with none severe indicating that all the combinations were safe. The cost effective analysis showed that combination of azithromyin and cefotaxime is most economical.
Keywords: Antibiotics; Organisms; Antibiotic use; Pediatrics